Los 7 habitos de los adolescentes altamente efectivos : la mejor guia practica para el exito juvenil - Covey, Sean. (Nueva York : Vintage Espanol, 2013)
Covey provides useful tips and life skills for young people to practice in their daily lives.
Includes bibliographical references (page 253) and index.
Keywords: Teenagers -- Conduct of life -- Juvenile literature; Success -- Psychological aspects -- Juvenile literature; Teenagers -- Life skills guides -- Juvenile literature; Conduct of life -- Juvenile literature; Teenagers -- Juvenile literature; Success -- Juvenile literature; Life skills -- Juvenile literature; Spanish language materials -- Juvenile literature